Productivity, Mortality, and Technology in European and US Coal Mining, 1800-1913 - Javier Silvestre (European Historical Economics Society (EHES), 2021)
European coal production underwent a period of dramatic increase from the early nineteenth century to 1913. A consensus exists, however, for a depiction of the coal industry as, to a high degree, technologically stagnant throughout the long nineteenth century. Macro-inventions, or general purpose technologies, in fact, appeared at either end of the period. In the interregnum, therefore, the increase in European coal production would have mainly been the result of adding more labor rather than developing new technology. This paper aims to revise this interpretation. First, long-term series of labor productivity and fatality rates data are presented. Second, a link between improvements in Europe both in productivity and safety in conjunction with a series of "small-scale", for the most part complementary to labor and closely related to questions of safety, technological innovations is proposed. A comparison of productivity and safety for European countries is established with the US.
Keywords: N70; N50; N30; Q35; O33; 330; Long nineteenth-century coal mining; productivity; mortality; technology; Europe; United States